Faktor-Faktor Status Gizi Kurang Pada Anak Usia Prasekolah di Wilayah Kerja Puskesmas Guguk Panjang Kota Bukittinggi - Novela, Vina; Kartika, Listiani (Jurnal Endurance, 2019)
Malnutrition in pre-school childrenstill found in Guguk Panjang Community Health Center. This data can be found from Bukittinggi Health Office in 2017 which stated that 800 under-fives children had less nutrition. In Guguk Panjang Community Health Centerin 2017, malnutrition cases were found in 162 people. This study aims to find out some factors related to malnutrition in the Guguk Panjang Community Health Center in 2018. The type of this research was descriptive analytic with a cross sectional study design.. The population in this reseacrh as many 1.106 population and 92 samples preschool-aged mothers. Then, the samples were taken from purposive sampling technique. The data were analyzed by univariate and bivariate by using Chi-Square statistical test. The results of this research showed that 54.3% of them had high level of knowledge. Then, 52.2% of themhad poor parenting. Next, the mothers did not provide exclusive breastfeeding were around 63.0%. Moreover, based on bivariate analysis there was a relationship between knowledge p value 0.008), parenting (p value 0.001) history of exclusive breastfeeding with malnutrition (p value 0.021). In short, it can be concluded that there were some factors related to malnutrition in preschool children. They were knowledge, parenting, and exclusive breastfeeding history. Then, it is expected that the health workers provide more information about nutrition and education about good parenting for children and also provide brochures or leaflets about nutrition.Kasus gizi kurang pada anak pra sekolah masih ditemukan diwilayah kerja puskemas guguk panjang. Hal ini terlihat data dari dinas kesehatan kota bukittinggi mencatat bahwa pada tahun 2017 balita dengan gizi kurang sebanyak 800 orang. Puskesmas guguk panjang pada tahun 2017 mempunyai gizi kurang sebanyak 162 orang. Tujuan penelitian, untuk mengetahui faktor-faktor yang berhubungan dengan gizi kurang pada anak prasekolah. Jenis penelitian ini adalah deskriptif analitik dengan desain cross sectional study. Populasi dalam penelitian sebanyak 1.106 orang dengan sampel 92 orang ibu anak prasekolah. Teknik pengambilan sampel porposive sampling. Pengolahan data dengan analisisunivariat dan bivariat  menggunakan uji statistik Chi - Square.Hasil penelitian menunjukkan terdapat 54,3% tingkat pengetahuan tinggi. Ibu yang pola asuh kurang baik sebanyak 52,2% . Ibu yang tidak memberikan ASI Ekslusif sebanyak 63,0%. Dari uji statistik didapatkan ada hubungan bermakna antara pengetahuan dengan gizi kurang (p value 0,008). Ada hubungan antara pola asuh dengan gizi kurang (p value 0,001) dan ada hubungan antara riwayat pemberian ASI Eksklusif dengan gizi kurang (p value,021).Disimpulkan bahwa faktor yang berhubungan dengan gizi kurang pada anak prasekolah adalah pengetahuan, pola asuh, dan riwayat pemberian ASI Eksklusif